Spanish Minors’ Perception of their Parents’ Role in their Use of Social Media Networks - Feijoo, Beatriz; Sádaba, Charo; López-Martínez, Adela (International and Multidisciplinary Journal of Social Sciences (RIMCIS), 2024)
The role of families in the use of media by children has traditionally been analyzed through different parental mediation strategies, and the most recent research pays attention to the impact of these practices on the generalization of digital media and, in particular of mobile devices and social media. With the aim of analyzing schoolchildren’s perception of the role their families especially parents— have in their management and handling of social networks content (challenges, publications, and monitoring of influencers, disinformation, and hoaxes), a qualitative study was carried out by holding 12 discussion groups among a sample of Spanish minors. Generally speaking, minors’ allusions to family converge to two dimensions: family as a resource for general information or verification (warnings on possible hacks, for example) or as a source of restrictions or limitations when parents deem content improper or excessive. An interesting finding was that minors perceive hoaxes as mostly coming through WhatsApp family groups. Remarkably, students tend to manage two profiles on the same social network: a public account where they friend their parents, and a private one, reserved only for close friends.
Percepción de los Menores Españoles sobre el Papel de sus Padres en su Uso de Redes Sociales
El papel de las familias en el uso que los menores hacen de los medios ha sido tradicionalmente analizado a través de distintas estrategias de mediación parental. La investigación más reciente presta atención al impacto que tiene en estas prácticas la generalización de los medios digitales y, en particular, de los dispositivos móviles y los medios sociales. En el presente artículo se busca analizar la percepción de menores españoles entre 11 y 17 años del papel de sus padres y madres en la gestión y manejo de contenido que ellos hacen de las redes sociales (challenges, publicaciones y seguimiento a influencers, desinformación, bulos). Para ello, se planteó un estudio cualitativo mediante la celebración de 12 grupos de discusión en los que las alusiones a la familia se centraron en dos dimensiones: como fuente de información a nivel general o como fuente de restricciones ante un uso que se cree excesivo. Asimismo, los menores perciben que los grupos familiares de WhatsApp son la vía por la cual reciben más bulos. Además, explicitan la tendencia a disponer de dos perfiles en una misma red social: una cuenta pública, más abierta en la que aceptan a sus padres, y una privada, que reservan sólo para las amistades cercanas.
Keywords: menores; redes sociales; mediación parental; competencia digital; Scopus; Emerging